2021
DOI: 10.3892/etm.2021.10255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the interstitial cells of Cajal in the gallbladder of guinea pigs fed a lithogenic diet

Abstract: Cholesterol cholelithiasis is a common disease and gallbladder hypomotility may underlie its pathogenesis. Interstitial cells of Cajal (ICCs) in the gallbladder serve vital roles in regulating gallbladder motility. The aim of the present study was to investigate changes in gallbladder ICCs during the development of cholesterol cholelithiasis. A total of 40 male guinea pigs were randomly assigned to four groups and fed a standard diet (SD) or lithogenic diet (LD) for 2 or 8 weeks. The LD significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Интересны экспериментальные данные об апоптозе клеток Кахаля в условиях гипернасыщенности желчи, которые есть в том числе и в гладкомышечных клетках желчного пузыря и выполняют функцию передачи сигнала [11]. Это может вносить дополнительный вклад в нарушение моторики.…”
Section: патогенез функциональной билиарной болиunclassified
“…Интересны экспериментальные данные об апоптозе клеток Кахаля в условиях гипернасыщенности желчи, которые есть в том числе и в гладкомышечных клетках желчного пузыря и выполняют функцию передачи сигнала [11]. Это может вносить дополнительный вклад в нарушение моторики.…”
Section: патогенез функциональной билиарной болиunclassified
“…With advances in recent research, it has been found that Interstitial Cells of Cajal (ICCs) play an important role in maintaining the normal motility of the gallbladder (Huang et al, 2009;Fu et al, 2021). For example, in guinea pigs with cholesterol cholelithiasis, the density and ultrastructure of ICCs in the gallbladder are altered (Huang et al, 2021). Chronic inflammatory response of the gallbladder also leads to ultrastructural damage of the ICCs which in turn affects the normal physiological function of the gallbladder smooth muscle, resulting in abnormal gallbladder activity (Zhang et al, 2022;Ding et al, 2023).…”
Section: Altered Biliary Tract Dynamics and The Formation Of Gallstonesmentioning
confidence: 99%
“…Hypercholesterolemia is an independent risk factor for cholelithiasis, as it may increase biliary cholesterol concentrations, consequently leading to bile crystallization and, ultimately, gallstone formation ( 179 , 180 ). More importantly, cholesterol accumulation strongly damaged the density and ultrastructure of GB ICCs by inhibiting the stem cell factor (SCF)/c-Kit pathway, and disrupted membrane receptor functions of STIN cells, particularly CCK1 receptors ( 181 - 183 ). Due to impaired CCK-induced emptying, the resulting GB stasis provides a microenvironment for excess cholesterol to remain in the lumen; in turn, the elevated cholesterol content further impairs GB emptying ( 184 ).…”
Section: Stin Syncytium and The Pathophysiology Of Gb Diseasesmentioning
confidence: 99%